Strategy of Managing A Globalizing Business - Weichai Engine - Wei, Ding; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2017)
Abstract - After over 120 years development, diesel engine industry improves and changes people‘s daily life continuously. Although grows up to an diversified group company recently, China Weichai is insisting on the engine manufacturing as the core product and business, which faces fierce competition in domestic market and strives to globalize development. Globalization can increase market size, enhance a product’s growth potential and optimize the location of value-chain activities. Weichai has drawbacks of late start, technology gap, strategic plan, cross culture and shortage of talents on the globalizing way. What's the direction and how to realize the international movement is an urgent question need to be solved. There are a large range of theories that embed international business world. OLI model includes three dimensions of ownership, location and internationalization advantages. It is the most complete theory until now to explain the internationalization directions. It concretes several steps of internationalization process that each company must comply in order to invest abroad properly. EPG Model is another international business framework, including ethnocentric, polycentric and geocentric three approaches. After the analysis of economy situation, risk and regulation, as well as the engine market performance and capacity, Weichai has more confidence of involving exporting, licensing and FDI activities. Ethnocentric approach will be a suitable globalization strategy to Weichai. Start with reorganization, market research, quality consistence improvement, service and spare parts networks, global branding and overseas talents recruitment, Weichai engine globalization strategy can be implemented in future.Key words: Business strategy, Internationalization, OLI model, EPG model